2023
DOI: 10.3390/ijms24032443
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Copper in the Hydrogenation of Furfural and Levulinic Acid

Abstract: Currently, there is a great interest in the development of sustainable and green technologies for production of biofuels and chemicals. In this sense, much attention is being paid to lignocellulosic biomass as feedstock, as alternative to fossil-based resources, inasmuch as its fractions can be transformed into value-added chemicals. Two important platform molecules derived from lignocellulosic sugars are furfural and levulinic acid, which can be transformed into a large spectrum of chemicals, by hydrogenation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 190 publications
0
6
0
Order By: Relevance
“…Copper catalysts with solid acid supports were shown to have a high activity towards the formation of cyclopentanone from furfural. 16 In this case, Cu is responsible for the hydrogenation of furfural to furfuryl alcohol and then the Lewis acid sites provided by the acidic support can accept the electron of the carbonyl group, favoring the rearrangement of furfuryl alcohol into cyclopentenone, which is finally hydrogenated to cyclopentanone. 16…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper catalysts with solid acid supports were shown to have a high activity towards the formation of cyclopentanone from furfural. 16 In this case, Cu is responsible for the hydrogenation of furfural to furfuryl alcohol and then the Lewis acid sites provided by the acidic support can accept the electron of the carbonyl group, favoring the rearrangement of furfuryl alcohol into cyclopentenone, which is finally hydrogenated to cyclopentanone. 16…”
Section: Resultsmentioning
confidence: 99%
“…Among these, copper-based catalysts are favoured (Table 2) mainly for the production of MF, but also for furfuryl alcohol and cyclopentanone production. 16 This is because copper-based catalysts have a lower hydrogenating capacity, which limits the C-C ring cleavage and promotes the formation of furfuryl alcohol and MF. 17 Regarding the reaction phase of furfural conversion to MF, vapor-phase processes appear more suitable in terms of MF selectivity.…”
Section: Introductionmentioning
confidence: 99%
“…As in the case of (E)-cinnamyl aldehyde (I) (see Table 1), the data achieved for the hydrogenation of levulinic acid (V) with Ru(0)-CS (see Table 2) are extremely interesting and reveal high performance compared to data in the literature [61,98,99]. In fact, Ndolomingo and co-workers recently reported a comparison between the efficiency values of different MNPs employed for the hydrogenation of (V) [91], and from this work it emerged that Ru@Meso-SiO 2 nanoparticles are among most efficient hydrogenation catalysts, leading to total substrate conversion and selectivity in (VI) at moderate p(H 2 ) (10 atm) and in a short time (5 h), yet very high temperatures are required (150 • C), and dioxane is used as a solvent [100].…”
Section: Scheme 3 Schematic Pathways Of Hydrogenation Reaction Of (E)...mentioning
confidence: 86%
“…Therefore, (E)-cinnamaldehyde (I) and levulinic acid (V) are commonly employed as standard substrates to study the efficiency of hydrogenation catalysts. It is interesting to note that, although many studies have been reported in the literature employing both noble and non-noble homogeneous and heterogeneous catalysts for the hydrogenation of (I) and (V) [55][56][57][58], to the best of our knowledge, chitosan nanoparticles have never been employed for the hydrogenation of (I) or (V) [59][60][61][62][63].…”
Section: Introductionmentioning
confidence: 99%
“…Catalysis is an advanced technology in both the chemical industry and academic research [1][2][3]. Transition-metal catalyzed organic transformations have attracted a great deal of attention for the efficient crack and formations of chemical bonds [4][5][6][7]; therefore, they have been widely applied in the research and development of drugs, pesticides, fine chemicals and other functional materials [8][9][10].…”
Section: Introductionmentioning
confidence: 99%